Effect of Yttrium on Microstructure and Hardness Properties of Aluminium LM30 Alloy - Sulaiman, Siti Sarah; Ahmad, Rosli (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The application of aluminium alloy in the automotive and aircraft industries has strengthened the need to investigate the influence of rare earth elements on aluminium alloys. A lightweight vehicle is one way for increasing a vehicle’s fuel efficiency and performance. Despite the increased interest in aluminium alloys, their applicability is still restricted in comparison to steel. The effect of Yttrium alloying addition elements on the microstructure and hardness properties of cast LM30 (Al-Si17Cu4Mg) alloy was studied. The purpose of this research is to investigate the variations that occurred in Si morphology as well as their effect on the hardness value. The experimental results indicate that the Yttrium affected the silicon eutectic morphology of Al-Si17Cu4Mg alloy when 1.0 wt. % was added to the alloy and the acicular structure of Si was modified into a fine fibrous structure. The hardness measurements revealed that the hardness values of the based alloy were higher with the Yttrium addition.